Risk factor prediction of severe postoperative acute kidney injury at stage 3 in patients with acute type A aortic dissection using thromboelastography - Guan, Xin-Liang; Li, Lei; Li, Hai-Yang; Gong, Ming; Zhang, Hong-Jia; Wang, Xiao-Long (Frontiers in Cardiovascular Medicine, 2023)
Objective: The perioperative blood transfusion and postoperative drainage volume are not only known risk factors for acute kidney injury (AKI) but also indirect markers of coagulopathy in patients with acute type A aortic dissection (ATAAD). However, the routine laboratory tests did not adequately reflect and assess the overall coagulopathy profile in patients with ATAAD. Thus, the objective of this study was to explore the association between hemostatic system and severe postoperative AKI (stage 3) in patients with ATAAD using thromboelastography (TEG). Methods: We selected 106 consecutive patients with ATAAD who underwent emergency aortic surgery from Beijing Anzhen Hospital. All participants were categorized into stage 3 and non-stage 3 groups. The hemostatic system was evaluated using routine laboratory tests and TEG preoperatively. We undertook univariate and multivariate logistic regression analysis to determine the potential risk factors for severe postoperative AKI (stage 3), with special investigate the association between hemostatic system biomarkers and severe postoperative AKI (stage 3). Receiver operating characteristic (ROC) curves were generated to assess the predictive ability of hemostatic system biomarkers for severe postoperative AKI (stage 3). Results: A total of 25 (23.6%) patients suffered severe postoperative AKI (stage 3) including 21 patients (19.8%) who required continuous renal replacement therapy (RRT). Multivariate logistic regression analysis demonstrated that preoperative fibrinogen level (OR, 2.02; 95% CI, 1.03 to 3.00; p = 0.04), platelet function (MA level) (OR, 1.23; 95% CI, 1.09 to 1.39; p = 0.001) and cardiopulmonary bypass (CPB) time (OR, 1.01; 95% CI, 1.00 to 1.02; p = 0.02) were independently associated with severe postoperative AKI (stage 3). The cutoff value of preoperative fibrinogen and platelet function (MA level) for predicting severe postoperative AKI (stage 3) were determined to be 2.56g/L and 60.7mm in the ROC curve [area under the curve (AUC): 0.824 and 0.829; p < 0.001]. Conclusions: The preoperative fibrinogen level and platelet function (MA level) were potential predictive indicator for the occurrence of severe postoperative AKI (stage 3) in patients with ATAAD. The TEG may be prospective technique for real-time monitoring and rapid measurement of hemostatic system to improve the postoperative outcomes of patients.